HUBUNGAN TINGKAT PENDIDIKAN IBU, STIMULASI, DAN STATUS GIZI DENGAN PERKEMBANGAN MOTORIK ANAK USIA 4 -5 TAHUN - Rahmadhani, Sendy Pratiwi; Yunola, Satra; Silaban, Titin Dewi Sartika (JOURNAL OF HEALTH SCIENCE, 2021)
Preschool age is the most important period in the formation of personality as the foundation for good physical health, if this is ignored will cause the child difficult to catch up. The purpose of this study is to find out the relationship of maternal education level, stimulation, and nutritional status with motoric develompment of children aged 4-5.This research is observational analytics with cross sectional design. The population in this study are mothers who had children aged 4-5 years. Sample was collected by using total sampling technique..The results of this study was obtained 27 (58.7%) mothers had a low level of education, 30 (65.2%) mother does not provide stimulation to her child, 31 (67.4%) children had normal nutritional status, and 28 (60.9%) children had age-appropriate development. Based on the chi-square statistical test there are relationship of maternal education level (p-value 0.032 ; OR = 0.255), stimulation (p-value 0.013 ; OR = 8,000), and nutritional status (p-value 0.000 ; OR = 94,000) with the motoric development of children aged 4-5 years. Advice for health workers who are health centre in order to improve health care programs, especially in early detection of children development andencourage mothers who have toddlers in order to provide good stimulation for them. Key Words: Education, Motoric development, Nutritional Status, Stimulation